Full-mouth rehabilitation with lithium disilicate ceramic crowns in hypoplastic amelogenesis imperfecta: a case report and review of literature - Ranran Chen; Ye Lin; Yi Sun; Xinni Pan; Yuedan Xu; Xiangxing Kong; Ling Zhang (BMC, 2024)
Abstract Background Amelogenesis imperfecta (AI) is a group of genetic disorders characterized by tooth discoloration and enamel defects. Patients with AI always exhibit generalized attrition and defective tooth structure, leading to the loss of occlusal vertical dimension (OVD). Appropriate rehabilitation is challenging and essential to improve patients' aesthetics and function. Case presentation This case report presents a comprehensive management of a 30-year-old woman with hypoplastic AI. A 52-month follow-up revealed satisfactory full-mouth rehabilitation performances of lithium disilicate ceramic crowns after clinical crown lengthening, with increased vertical dimension. Conclusions Patients with severe hypoplastic AI require proper full-mouth rehabilitation. Using full-crown lithium disilicate restorations to increase the OVD by 2‒4 mm is a safe and predictable recommendation for such cases. In addition, patients with AI require complex and comprehensive management. The long-term effects of full-mouth rehabilitation with lithium disilicate ceramic crowns still necessitate further follow-ups.